2014
DOI: 10.1002/oby.20757
|View full text |Cite
|
Sign up to set email alerts
|

Role of child weight status and the relative reinforcing value of food in children's response to portion size increases

Abstract: Objective Food portion size is an important determinant of intake in children. It remains unknown if children’s weight status and relative reinforcing value of food (RRVF) interact with portion size to affect intake. Design and Methods In a randomized crossover design, 25 normal-weight and 25 obese children, ages 8 to 10 years, consumed dinner once a week for 3 weeks. At each dinner, the same meal was served, but the portion size of all foods (chicken nuggets, hash browns, ketchup, green beans, brownies) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 23 publications
(30 reference statements)
2
33
0
Order By: Relevance
“…The other 11 of the 83 eligible studies (12 study reports) were identified by the updated search (30 January 2015) (Bajaj 2014; Haire 2014; Kral 2014; Marchiori 2014; Rolls 2014a; Smith 2013a; van Ittersum 2013; van Kleef 2014; Wansink 2013; Wansink 2014; Williams 2014). These 11 studies, published during 2013 and 2014, are described in Characteristics of studies awaiting classification tables and are recorded as 'studies accepted into the review and awaiting full integration' in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 11 of the 83 eligible studies (12 study reports) were identified by the updated search (30 January 2015) (Bajaj 2014; Haire 2014; Kral 2014; Marchiori 2014; Rolls 2014a; Smith 2013a; van Ittersum 2013; van Kleef 2014; Wansink 2013; Wansink 2014; Williams 2014). These 11 studies, published during 2013 and 2014, are described in Characteristics of studies awaiting classification tables and are recorded as 'studies accepted into the review and awaiting full integration' in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore consider it improbable that we have failed to identify sufficient relevant evidence to substantively alter our conclusions. The scope, scale and complexity of this review and its analysis meant that we took the pragmatic decision (in consultation with the Cochrane Public Health Review Group) to defer full integration of 11 further eligible studies identified by the updated search (30 January 2015) (Bajaj 2014; Haire 2014; Kral 2014; Marchiori 2014; Rolls 2014a; Smith 2013a; van Ittersum 2013; van Kleef 2014; Wansink 2013; Wansink 2014; Williams 2014), until the first major update of this review. However, the results of preliminary analyses of outcome data that could provisionally be extracted from each of these 11 further eligible studies (see Appendix 2) establish that there is minimal potential for the full integration of these studies to change the interpretation of the results of this review, and hence its conclusions, as currently reported in the Results, Discussion and Authors' conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…To be included, children had to be: 8 to 10 years and normal-weight or obese. For additional details regarding inclusion criteria, see Kral and colleagues (2014). Children were excluded from the study if they had medical conditions or were taking medications known to affect food intake or body weight; were overweight; were diagnosed with a learning disability or sight/hearing impairment; had food allergies/intolerances; or were on a special diet.…”
Section: Methodsmentioning
confidence: 99%
“…For example, when the portion size of three fruit and vegetable side dishes was doubled at a meal, Kral et al [109] demonstrated that overweight and obese children showed an almost three times greater increase in intake of those foods compared to normal-weight children. Similarly, data from two recent laboratory studies also indicate that obese children, in particular, may be more susceptible to overeating when served large portions of palatable energy-dense foods [110,111] . Whether genes for FISR influence children's responsiveness to large food portions remains to be seen.…”
Section: Parental Feeding Styles Food Portioning and Fisrmentioning
confidence: 99%